1999
DOI: 10.1097/00000542-199902000-00025
|View full text |Cite
|
Sign up to set email alerts
|

The Antiallodynic Effects of Intrathecal Cholinesterase Inhibitors in a Rat Model of Neuropathic Pain 

Abstract: These experiments suggest that intrathecal edrophonium or neostigmine produces an antagonism on touch-evoked allodynia at the spinal level in a rat model of neuropathic pain and that the antiallodynic action of cholinesterase inhibitors is probably mediated by a spinal muscarinic system, especially at the M1 receptor subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 39 publications
5
31
0
Order By: Relevance
“…In the SNL model of neuropathic pain, we demonstrate that WAY-132983 fully reversed the tactile allodynia, a clinical hallmark of neuropathic pain. Although the effects of muscarinic agonists in the SNL model have not been reported previously, our observations are consistent with the reported effects of cholinesterase inhibitors in the SNL model (Lavand'homme et al, 1998;Chiari et al, 1999;Hwang et al, 1999). Furthermore, cholinomimetics reverse the tactile allodynia seen in streptozotocin-induced diabetic rats (Chen et al, 2001), and an increase in mAChR expression levels (Chen and Pan 2003) makes it tempting to speculate that muscarinic agonists may be effective in the treatment of diabetic neuropathy.…”
Section: Discussionsupporting
confidence: 91%
“…In the SNL model of neuropathic pain, we demonstrate that WAY-132983 fully reversed the tactile allodynia, a clinical hallmark of neuropathic pain. Although the effects of muscarinic agonists in the SNL model have not been reported previously, our observations are consistent with the reported effects of cholinesterase inhibitors in the SNL model (Lavand'homme et al, 1998;Chiari et al, 1999;Hwang et al, 1999). Furthermore, cholinomimetics reverse the tactile allodynia seen in streptozotocin-induced diabetic rats (Chen et al, 2001), and an increase in mAChR expression levels (Chen and Pan 2003) makes it tempting to speculate that muscarinic agonists may be effective in the treatment of diabetic neuropathy.…”
Section: Discussionsupporting
confidence: 91%
“…In formalin test, choline did have an effect in the second phase. M1 mAChRs in sheep (Bouaziz et al 1995) and rats (Naguib and Yaksh 1997) and M3 mAChRs have been suggested to be involved mainly in spinal antinociception (Hwang et al 1999). nAChRs are extensively distributed in central nervous system (CNS) and peripheral sites.…”
Section: Discussionmentioning
confidence: 99%
“…1 7 A previous study suggested that muscarinic stimulation of critical spinal sites resulted in the activation of local lumbar cholinergic circuits that might modulate the local transmission of the afferent allodynic information. 8 Considerable evidence exists that the muscarinic cholinergic system of the lumbar spinal cord is intrinsic 18,19 and that the cholinergic innervation of the intermediolateral cell column (IML) is from a source intrinsic to the spinal cord. 19,20 A recent study by Pan et al, 7 found that spinally released acetylcholine plays a role in the antiallodynic effect of IT clonidine in neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 IT administration of cholinesterase inhibitors displays a dose-dependent antiallodynic effect, which is mediated by the spinal muscarinic receptor system. 8 Carbachol is a nonspecific cholinergic agonist with a prominent muscarinic effect. 9 Owing to the hydrophilic properties of carbachol it may have a long duration of action after IT administration.…”
mentioning
confidence: 99%